Markers of early changes in cognition across cohorts of adults with Down syndrome at risk of Alzheimer's disease. Issue 1 (2nd May 2021) - Aschenbrenner, Andrew J.; Baksh, R. Asaad; Benejam, Bessy; Beresford‐Webb, Jessica A.; Coppus, Antonia; Fortea, Juan; Handen, Benjamin L.; Hartley, Sigan; Head, Elizabeth; Jaeger, Judith; Levin, Johannes; Loosli, Sandra V.; et al.
Abstract: Introduction: Down syndrome (DS), a genetic variant of early onset Alzheimer's disease (AD), lacks a suitable outcome measure for prevention trials targeting pre‐dementia stages. Methods: We used cognitive test data collected in several longitudinal aging studies internationally from 312 participants with DS without dementia to identify composites that were sensitive to change over time. We then conducted additional analyses to provide support for the utility of the composites. The composites were presented to an expert panel to determine the most optimal cognitive battery based on predetermined criteria. Results: There were common cognitive domains across site composites, which were sensitive to early decline. The final composite consisted of memory, language/executive functioning, selective attention, orientation, and praxis tests. Discussion: We have identified a composite that is sensitive to early decline and thus may have utility as an outcome measure in trials to prevent or delay symptoms of AD in DS.